Co-expression of different angiogenic factors in external auditory canal cholesteatoma - Naim, Ramin; Riedel, Frank; Götte, Karl; Bran, Gregor M.; Sadick, Haneen; Gößler, Ulrich; Hörmann, Karl (Acta oto-laryngologica, 2004)
Objective Although external auditory canal cholesteatoma (EACC) was first described in 1850, its cause remains surprisingly unclear. Angiogenesis, the formation of new blood vessels, is essential to normal development and wound healing in adults. Abnormal regulation of angiogenesis has been implicated in the pathogenesis of several disorders. The aim of this study was to analyse angiogenesis regulator expression in EACC. Materials and Methods Cryostat sections of 13 investigated EACC tissue samples and normal control tissue were immunostained for angiogenic hepatocyte growth factor (HGF)/scatter factor (SF), its c-Met receptor and vascular endothelial growth factor (VEGF) using a standard streptavidin-biotin complex procedure. Staining against von Willebrand factor (vWF) served as an endothelial marker. Statistical analysis was performed semiquantitatively. Results The assayed angiogenic factors were all present in the EACC tissue, and partly overexpressed. vWF was detected in the apical layers of the matrix epithelium. Positive immunoreactivity for c-Met and VEGF was detectable in all layers of the EACC epithelium; however, adjacent tissue did not express c-Met and VEGF. HGF/SF was predominantly expressed in the adjacent perimatrix tissue and fibroblasts in particular were stained positive. Conclusions The presence of vWF in the apical part of the matrix depicted the attempt at angiogenesis in this part of the EACC. The detection of VEGF and c-Met in the epithelial part of the EACC implied that their origin may be epithelial, while HGF/SF may be secreted or stored in the adjacent mesenchymal EACC tissue. The angiogenic factors investigated seem to play an important role in establishing that EACC occurs by modulation of angiogenesis.
Elektronische Reproduktion der Druckausgabe
Gesehen am 08.04.2022